Biochemical constituents of Excoecaria agallocha L. under diff erent levels of NaCl stress - Sozharajan, R.; Natarajan, S. (Current Botany)
The present investigation was made to study the effect of different concentrations of NaCl on biochemical constituents of the seedlings of Excoecaria agallocha. The plant could survive a wide range of 100-1000 mM NaCl concentrations. The upper limit for the survival of the seedlings was 500 mM NaCl. Above 500 mM, the seedlings did not survive. The plant parts (leaf, stem, and root) of after salt treatment 60 days, old plants were used for the analysis of biochemical activities. The NaCl promoted the compatible solutes such as starch, proline, and protein. The Sugar content decreased up to the optimum level of 300 mM NaCl and increased at the higher concentrations. The starch and chlorophyll content increased up to 300 mM NaCl, beyond 300 mM, the contents decreased marginally. The proline content increased with the increasing salinity. The protein increased with increasing salt concentration up to the optimal level of 300 mM NaCl, and decreased at the higher concentrations. The plant can able to survive up to 500 mM NaCl concentration and remarkable accumulations of compatible solute make the plant survive salinity stress.